Minimally invasive Ivor Lewis esophagectomy in a patient with situs inversus totalis through a total of five ports - DURUSOY, ALİ; ASLAN, SEZER (My University, 2022)
Situs inversus totalis is inverse placement of intra-thoracic and abdominal organs identical with a mirror image. Herein, we present a rare case of situs inversus totalis and gastroesophageal junction carcinoma treated with minimally invasive Ivor Lewis esophagectomy. A 73-year-old male patient presented with dysphagia and a diagnosis of adenocarcinoma was made. He underwent three-port laparoscopic gastric conduit preparation without using a liver retractor. Esophageal mobilization in the chest was completed with biportal video-assisted thoracoscopic surgery technique and a completely side-to-side stapled anastomosis. The patient is still alive without recurrence four years after surgery. Minimally invasive Ivor Lewis esophagectomy can be performed in these cases; however, a careful planning and rethinking of the anatomy for correct intraoperative orientation are needed. Similar surgical and oncological outcomes are expected in this patient population.
Keywords: Tıp; Sağlık Bilimleri; Cerrahi Tıp Bilimleri; Medicine; Health Sciences; Surgery Medicine Sciences; CERRAHİ; Klinik Tıp; Klinik Tıp (MED); SURGERY; CLINICAL MEDICINE; Clinical Medicine (MED); Surgery; Esophagectomy; minimally invasive; situs inversus totalis; LAPAROSCOPIC GASTRIC MOBILIZATION; THORACOSCOPIC ESOPHAGECTOMY; CANCER